2021
DOI: 10.3389/fcell.2021.780422
|View full text |Cite
|
Sign up to set email alerts
|

It Cuts Both Ways: An Annelid Model System for the Study of Regeneration in the Laboratory and in the Classroom

Abstract: The mechanisms supporting regeneration and successful recovery of function have fascinated scientists and the general public for quite some time, with the earliest description of regeneration occurring in the 8th century BC through the Greek mythological story of Prometheus. While most animals demonstrate the capacity for wound-healing, the ability to initiate a developmental process that leads to a partial or complete replacement of a lost structure varies widely among animal taxa. Variation also occurs withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 99 publications
(181 reference statements)
0
13
0
Order By: Relevance
“…In addition, using RNAi-mediated knockdown, we showed that the gradual accumulation of Ej-soxC-expressing cells in the head blastema was facilitated by MMPreg, a member of the matrix metalloprotease (MMP) family of extracellular proteases that are major executors of extracellular matrix remodeling 24 . Our results showed that the gradually accumulated soxC-expressing cells constituted a large part of the blastema, suggesting that the population of soxC-expressing cells represents the blastema (historically called the blastemal mass in annelid 25 ). At the same time, the evidence shown here suggests that the soxC-expressing cells attached to the body wall are the cellular source of blastema and proves that the soxC-expressing cells represent the "migrating cells" during blastema formation that several researchers have speculated for over 130 years.…”
Section: Introductionmentioning
confidence: 72%
“…In addition, using RNAi-mediated knockdown, we showed that the gradual accumulation of Ej-soxC-expressing cells in the head blastema was facilitated by MMPreg, a member of the matrix metalloprotease (MMP) family of extracellular proteases that are major executors of extracellular matrix remodeling 24 . Our results showed that the gradually accumulated soxC-expressing cells constituted a large part of the blastema, suggesting that the population of soxC-expressing cells represents the blastema (historically called the blastemal mass in annelid 25 ). At the same time, the evidence shown here suggests that the soxC-expressing cells attached to the body wall are the cellular source of blastema and proves that the soxC-expressing cells represent the "migrating cells" during blastema formation that several researchers have speculated for over 130 years.…”
Section: Introductionmentioning
confidence: 72%
“…Remarkably, these worms can regenerate into a complete worm from each segment when cut into more than a dozen pieces, a process known architomy fission. 68 Annelids have a long history of study, dating back to the 18th century, with a focus on their extraordinary regenerative abilities. For an extensive and detailed history of these incredible worms up to 2021, readers are encouraged to refer to the works of Rota 69 and Martinez et al 68 Additionally, we acknowledge Charles Drewes’ passionate and inspiring contribution in proposing blackworms as a resilient and accessible organism for teaching and for research.…”
Section: From Single Individual Worm To Entangled Worms: the Blobmentioning
confidence: 99%
“…For instance, planarian or annelid worms are able to rebuild their entire body [ 41 , 42 ] with an immune system based on phagocytic cells and immunomodulators used as immunosuppressive therapy in humans [ 43 ]. Alike the immune system in humans, salamanders possess a complex network of innate and adaptive immune cells [ 44 ].…”
Section: Immunosuppressive Immune Response Correlates With a Higher R...mentioning
confidence: 99%